Analisis Proses Pembelajaran Pendidikan Agama Islam (PAI) Berbasis Kurikulum 2013 Di SDN 02 Tanjung Raja - Dwi Andini; Anggie Ratiwi; Doris Dwi Nanda; M.Husni Thamrin; Zulhadi Zulhadi; Dwi Noviani (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Islamic religious education (PAI) subjects have an important role in instilling spiritual and moral values in students. One of the components that supports implementing Islamic religious education (PAI) in schools is the curriculum. The aim of this research is to find out whether the implementation of Islamic religious education (PAI) learning at SDN 02 Tanjung Raja based on the 2013 curriculum is running well or not. This research uses qualitative research methods with a descriptive type. The data collection is through interview and observation techniques. The result of this research show that the implemented quite well, even though there are several obstacles faced, but they can be overcome with the best solution.